2008
DOI: 10.1021/jp807862m
|View full text |Cite
|
Sign up to set email alerts
|

SERR-Spectroelectrochemical Study of a cbb3 Oxygen Reductase in a Biomimetic Construct

Abstract: The cbb3 oxygen reductase from Bradyrhizobium japonicum was immobilized on nanostructured silver electrodes by anchoring the enzyme via a His-tag to a Ni-NTA coating, followed by reconstitution of a lipid bilayer. The immobilized enzyme retains the native structure and catalytic activity as judged by in situ surface-enhanced vibrational spectroscopy and cyclic voltammetry, respectively. Spectroelectrochemical titrations followed by SERR spectroscopy of the integral enzyme and its monohemic (fixO) and dihemic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 42 publications
3
64
0
Order By: Relevance
“…Spectra taken at sufficiently negative and positive potentials should be similar to spectra obtained in presence of a chemical reductant (dithionite) and oxidant (ferrocyanide), respectively. Such analyses were reported for cco in ptBLM assemblies Hrabakova et al , 2006 ;Todorovic et al , 2008 ) and confirmed that the structure of these proteins is largely preserved after immobilization.…”
Section: Surface-enhanced Resonance Raman and Ftir Difference Spectrosupporting
confidence: 78%
See 2 more Smart Citations
“…Spectra taken at sufficiently negative and positive potentials should be similar to spectra obtained in presence of a chemical reductant (dithionite) and oxidant (ferrocyanide), respectively. Such analyses were reported for cco in ptBLM assemblies Hrabakova et al , 2006 ;Todorovic et al , 2008 ) and confirmed that the structure of these proteins is largely preserved after immobilization.…”
Section: Surface-enhanced Resonance Raman and Ftir Difference Spectrosupporting
confidence: 78%
“…These bands correspond to the C = O stretching and N-H in-plane bending vibrations, respectively, of the polypeptide chain (Barth , 2007 ). Within these lines, it was confirmed that the transmembrane helices of the cbb 3 oxidase adopt a near-normal orientation relative to the gold surface in protein-tethered BLM assemblies (Todorovic et al , 2008 ). Importantly the techniques allow the protein to be reconstituted in phospholipid membranes and thus allow us to study the effect of the membrane on the properties of the proteins.…”
Section: Surface-enhanced Resonance Raman and Ftir Difference Spectromentioning
confidence: 74%
See 1 more Smart Citation
“…A similar approach was applied to a fumarate reductase immobilized on Au electrode with hydrophobic coating (Kinnear and Monbouquette, 1993). An alternative immobilization method has been developed for proteins that contain a genetically introduced His tag Ataka et al, 2004;Giess et al, 2004;Hrabakova et al, 2006;Todorovic et al, 2008). After functionalizing the solid support with Ni (or Zn) NTA (3,3´-dithiobis[N-(5amino-5-carboxy-pentyl)propionamide-N, N´-diacetic acid)] dihydrochloride) monolayer, the protein can be attached via His coordination to the Ni center, Figure 3C.…”
Section: Immobilization Of Membrane Proteinsmentioning
confidence: 99%
“…It is purified from an organism that is capable of growing heterotrophically via fermentation and aerobic and anaerobic respiration, with a genetically introduced His-tag, allowing immobilization of the CcO on a metal electrode via Ni-NTA SAMs, Figure 3C Giess et al, 2004;Hrabakova et al, 2006;Todorovic et al, 2008). The protein was specifically attached, uniformly oriented and catalytically active in the biomimetic construct.…”
Section: Wwwintechopencommentioning
confidence: 99%